1998
DOI: 10.1073/pnas.95.5.2621
|View full text |Cite
|
Sign up to set email alerts
|

Unequal representation of cardinal and oblique contours in ferret visual cortex

Abstract: We have measured the amount of cortical space activated by differently oriented gratings in 25 adult ferrets by optical imaging of intrinsic signal. On average, 7% more area of the exposed visual cortex was preferentially activated by vertical and horizontal contours than by contours at oblique angles. This anisotropy may ref lect the real-world prevalence of contours in the cardinal axes and could explain the greater sensitivity of many animals to vertical and horizontal stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
123
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(150 citation statements)
references
References 27 publications
24
123
1
2
Order By: Relevance
“…Further, cardinal contours produce larger cortical representations in imaging studies (Chapman and Bonhoeffer, 1998;Coppola et al, 1998;Dragoi et al, 2001;Wang et al, 2003;Yacoub et al, 2008) and ongoing fluctuations appear to be more often correlated with cardinal than with oblique maps (Kenet et al, 2003). Our data largely confirm the latter observation.…”
Section: Lateral Connections Account For a Cardinal Bias In Spontaneosupporting
confidence: 80%
“…Further, cardinal contours produce larger cortical representations in imaging studies (Chapman and Bonhoeffer, 1998;Coppola et al, 1998;Dragoi et al, 2001;Wang et al, 2003;Yacoub et al, 2008) and ongoing fluctuations appear to be more often correlated with cardinal than with oblique maps (Kenet et al, 2003). Our data largely confirm the latter observation.…”
Section: Lateral Connections Account For a Cardinal Bias In Spontaneosupporting
confidence: 80%
“…The final orientation preference distribution is also biased towards horizontal and vertical, as seen in ferret visual cortex (Coppola et al 1998). These results are the main novel component of the orientation map simulations.…”
Section: Orientation Map Experimentsmentioning
confidence: 53%
“…by suturing their eyelids shut, have few orientation-selective neurons in V1 as an adult (Blakemore and van Sluyters 1975;Crair et al 1998). Even in normal adult animals, the distribution of orientation preferences is slightly biased towards horizontal and vertical contours (Chapman and Bonhoeffer 1998;Coppola et al 1998). Such a bias would be expected if the neurons learned orientation selectivity from typical environments, which have more horizontal and vertical contours than oblique ones (e.g.…”
Section: Orientation Map Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous observations (Furmanski and Engel 2000;Li et al 2003;Wang et al 2003;Xu et al 2006) have revealed that there is more 'neural machinery' devoted to processing the cardinal (horizontal and vertical) orientations than the oblique orientations; these results have been related to the greater psychophysical sensitivity to cardinal than oblique orientations ('the oblique eVect'; Appelle 1972).The higher activation to vertical than horizontal patterns might be taken to similarly reXect an imbalance in the number of neurons that prefer each orientation. However, a single unit study in cat V1 (Li et al 2003) found a greater abundance of neurons tuned to horizontal than to vertical orientations and studies in ferret V1 have shown that larger cortical areas are devoted to horizontal than to vertical orientations (Chapman and BonhoeVer 1998;Coppola et al 1998). In contrast, a recent study using high-Weld fMRI in humans (Yacoub et al 2008) found that there was a bias towards vertical stimuli (with horizontal motion) among orientation-selective columns in V1 (although only a subsection of V1 was analysed in this study).…”
Section: Discussionmentioning
confidence: 99%